PMP Pencegahan Stunting Melalui Edukasi dan Skrining Kecacingan pada Ibu Hamil di Desa Biring Je’ne Moncongloe - Hasriani Saleng; Miladiarsi; Ayu Lestari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Stunting is a failure in children's growth and development experienced by children under the age of five due to a lack of nutritional intake when the fetus is in the womb until the beginning of the baby's birth and begins to appear until the baby is two years old. Mothers' lack of knowledge is a risk factor for stunting and providing education is one way to overcome stunting. The aim of this service is to increase public knowledge and awareness, especially for pregnant women, to find out about efforts to prevent stunting. The service method is carried out by providing education through counseling. The participants who attended this service were pregnant women, 40 participants took part in the service. Univariate data analysis using a descriptive approach and bivariate testing using the Paired T test. The results of service are increased knowledge after providing education. The test results obtained a P Value of 0.000 or there was an influence of education on participants' knowledge.